THE NOTION OF “GENDER” IN LINGUISTICS: THE NOTION OF “GENDER” IN LINGUISTICS - Sailaubaeva, Gozzal (Журнал иностранных языков и лингвистики, 2025)
By developments in every sphere, there are further questions and novelties in that areas including science. Due to the issues that are arisen in linguistics, sociolinguistics, philosophy and by having democracy in each sphere of the developing world, nowadays the term “gender” or “gender equality” uses more often than before. The word “gender” refers to characteristics of women, men, girls and boys that are socially constructed [8]. To understand what linguists mean by “gender”, a good starting point is Hockett’s definition: “Gender are classes of nouns reflected in behavior of associated words” [1:2]. The word “gender” is not used for just a group of nouns but also for the whole category, thus we may say that a particular language has, say, three genders, masculine, feminine, and neutral, and that the language has the category of gender [7]. Gender characterizes not only biological differences between male and female but also it has further meaning and definitions in linguistics according to their usage, especially in phraseological units and proverbs. This lead to blossom new branch in linguistics as gender linguistics and formation and active development of which falls at the end of the XX century [